2021
DOI: 10.1021/acs.jmedchem.1c00104
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and In Vivo Anti-inflammatory Activity Evaluation of a Novel Non-peptidyl Non-covalent Cathepsin C Inhibitor

Abstract: Cathepsin C (Cat C) participates in inflammation and immune regulation by affecting the activation of neutrophil serine proteases (NSPs). Therefore, cathepsin C is an attractive target for treatment of NSP-related inflammatory diseases. Here, the complete discovery process of the first potent "non-peptidyl non-covalent cathepsin C inhibitor" was described with hit finding, structure optimization, and lead discovery. Starting with hit 14, structure-based optimization and structure−activity relationship study we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Other CTSC inhibitors have not shown strong clinical translation, for example GSK-2793660 [193], which failed due to minimal effects on NSP activity. More recent work has shown that non-peptidyl, non-covalent inhibitors of CTSC can also effectively reduce NSP activity and may be more metabolically stable than their covalent counterparts [194,195]. Overall, CTSC inhibition represents a promising option for the treatment of inflammatory lung diseases, potentially having more consistent and far-reaching effects than NSP-specific inhibitors [110][111][112]116].…”
Section: Cathepsin Cmentioning
confidence: 99%
“…Other CTSC inhibitors have not shown strong clinical translation, for example GSK-2793660 [193], which failed due to minimal effects on NSP activity. More recent work has shown that non-peptidyl, non-covalent inhibitors of CTSC can also effectively reduce NSP activity and may be more metabolically stable than their covalent counterparts [194,195]. Overall, CTSC inhibition represents a promising option for the treatment of inflammatory lung diseases, potentially having more consistent and far-reaching effects than NSP-specific inhibitors [110][111][112]116].…”
Section: Cathepsin Cmentioning
confidence: 99%
“…88497-27-2, molar mass 173.99 g mol –1 , IUPAC name: pyridazine, 3-amino-6-bromo-, molecular structure is shown in Figure ) is a pyridazine derivative and an inhibitor of various enzymes. For example, it treats diseases related to the pancreas by inhibiting the activity of heterocyclic kinases. It can also inhibit the activity of glutaminase to achieve the purpose of inhibiting the proliferation of tumor cells, which is an effective means to treat various cancers such as liver cancer and pancreatic cancer. In addition to being an inhibitor of enzyme activity, it also can treat Huntington’s disease by promoting the synthesis of kynurenine monooxygenase. , Besides, it is the nemesis of some retroviruses, the working mechanism is that the replication of the virus can be effectively controlled by it…”
Section: Introductionmentioning
confidence: 99%